Biosafety Profiling of “Makann”, a Bi-herbal Formulation in Histopatology of the Brain and Uterus - Itemire, Anne Oghenekevwe; Idu, MacDonald; Enitome, Bafor Evi; Eze, Gerald Ikechi; Gabriel, Benjamin Ogunma (African Journal of Sciences and Traditional Medicine, 2025)
The biosafety of Garcinia kola and Carica papaya aqueous root extract "makann," a bi-herbal formulation, on the brain and uterus of female mice was examined. Plant roots were harvested, washed, shade-dried, and processed into an aqueous formulation extract. The bi-herbal formulation extract was administered orally at a dose of 2 g/kg in the treatment groups, as a single dose for 24 hr and 14 days, with a daily dose of 2 g/kg for 14 days. The investigation measured body weight, temperature, hematological parameters, organ weights (brain and uterus), and histology of the organs using standard experimental techniques. The results revealed no significant changes in body weight and temperature in the treated animals compared to the control group in all treatment groups. Hematological parameters in the 24-hour treated group showed a significant increase in white blood cell count, lymphocytes, red blood cell count, hemoglobin levels, and mean corpuscular hemoglobin concentration compared to the control (p<0.05). However, in 24-hr single, 14-day single and 14-day daily doses, platelet count was significantly increased. The organ weights of the brain and utserus showed no significant difference in bi-herbal formulation extract-treated groups compared with the control group (p<0.05). Histopathological evaluations of the examined organs did not reveal any lesions or signs of toxicity in the brain and uterus across all treatment groups compared to the control. In conclusion, the non-adverse changes in the parameters studied suggest that the bi-herbal formulation at 2 g/kg and for a period not more than 2 weeks may exhibit minimal or no toxicity, and its effect on long-term use should be investigated.